Analisis Alat Bantu Pemutar Es Puter Dengan Penggerak Motor Listrik 1 HP - Atikah Ayu Janitra; Ahmad Abdul Na’im (Journal of Mechanical Engineering and Applied Technology, 2023)
Snow ice is a type of ice that is liked by the public, especially teenagers, so it requires more production, while the manufacturing process in UKM is still manual by rotating the dough tube between buckets filled with ice cubes by using the hand as a spinner, so it is considered inefficient because it requires a relatively long time and causes fatigue from the workers, a tool or snow ice machine is made so that it can speed up and facilitate and improve efficiency in the production or processing process. Referring from various sources, namely observation, field studies, literature studies, machine design, and machine testing. So that it can be implemented and produces a tool that can be produced to facilitate the process of making snow ice and has dimensions of length = 560 [mm], width = 680 [mm] and height 1400 [mm]. With a dough capacity of 12.85 [kg], it requires 1 [HP] of power and takes 70-90 minutes to make snow ice freeze.